Women and the Catholic church negotiating identity and agency - McEwan, Tracy (London New York Bloomsbury Academic, 2025)
How do Catholic women make sense of their involvement in a church with restrictive gendered roles and responsibilities? Is there a vision for church which might provide Catholic women with a community of hope, justice and flourishing? Introducing a new methodological approach to studying Catholic women, this open access book provides fresh insights into women’s religious and spiritual experiences and church participation. Drawing on a case study of Australian Catholic women, Tracy McEwan develops the notion of “technologies of Catholicism” to explore the ways in which women shape their religious and secular identities against the backdrop of a masculinist Church. This book is a key resource for those seeking to understand women’s struggle to negotiate the impact of Catholicism and its oppressive gendered theologies. It introduces the term “everyday spiritual abuse” to explain the harm Catholic women experience on a day-to-day basis as they negotiate multiple material, spiritual, and structural inequalities. It proposes an alternative feminist model of church, which is contained and produced in the herstories of women.
Wie verstehen katholische Frauen ihr Engagement in einer Kirche mit restriktiven geschlechtsspezifischen Rollen und Verantwortlichkeiten? Gibt es eine Vision für Kirche, die katholischen Frauen eine Gemeinschaft der Hoffnung, Gerechtigkeit und des Gedeihens bieten könnte? Dieses frei zugängliche Buch stellt einen neuen methodischen Ansatz zur Erforschung katholischer Frauen vor und bietet neue Einblicke in die religiösen und spirituellen Erfahrungen und die Kirchenbeteiligung von Frauen. Anhand einer Fallstudie australischer katholischer Frauen entwickelt Tracy McEwan den Begriff der „Technologien des Katholizismus“, um zu untersuchen, wie Frauen ihre religiöse und säkulare Identität vor dem Hintergrund einer maskulinistischen Kirche gestalten. Dieses Buch ist eine wichtige Ressource für alle, die den Kampf von Frauen verstehen wollen, mit den Auswirkungen des Katholizismus und seiner unterdrückerischen geschlechtsspezifischen Theologien umzugehen. Es führt den Begriff „alltäglicher spiritueller Missbrauch“ ein, um den Schaden zu erklären, den katholische Frauen täglich erfahren, wenn sie mit vielfältigen materiellen, spirituellen und strukturellen Ungleichheiten zu kämpfen haben. Es schlägt ein alternatives feministisches Kirchenmodell vor, das in den Geschichten von Frauen verankert ist und in ihnen entsteht. [Mit KI übersetzt]
1: Introduction -- 2: Identity and authority -- 3: Magisterial ecclesiology: Virgin, bride, mother -- 4: Theorising power/knowledge for a feminist study of women in Catholicism -- 5: Invented identities -- 6: Enacting agency -- 7: The consequences of a lack of recognisability -- 8: A place where Catholic women might flourish -- Afterword -- References -- Index.
Includes bibliographical references and index
Keywords: Catholic Church -- Doctrines; Église catholique - Doctrines; Women in the Catholic Church; Women -- Religious aspects -- Catholic Church; Femmes dans l'Église catholique; Femmes - Aspect religieux - Église catholique; Roman Catholicism, Roman Catholic Church; domestic violence; Gender studies: women